2022
DOI: 10.1039/d1ta07128a
|View full text |Cite
|
Sign up to set email alerts
|

Investigating oxygen reduction pathways on pristine SOFC cathode surfaces by in situ PLD impedance spectroscopy

Abstract: Temperature and p(O2) dependences of the oxygen exchange kinetics of SOFC cathode materials were correlated with point defect concentrations. Defect chemical contributions were identified as a major part of effectively measured activation energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 77 publications
6
45
0
Order By: Relevance
“… 9 An in-depth mechanistic discussion of the relation between polarization resistance and defect chemistry is beyond the scope of the present work but can be found in a separate study. 20 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 An in-depth mechanistic discussion of the relation between polarization resistance and defect chemistry is beyond the scope of the present work but can be found in a separate study. 20 …”
Section: Resultsmentioning
confidence: 99%
“…This way of normalization has already been proven meaningful in previous studies, where it was demonstrated that only the area above the YSZ is electrochemically active for oxygen reduction, while the regions above the current collector grid are inactive due to relatively low ionic in-plane conduction. 8 The surface-related polarization resistances of all materials at 0. of the relation between polarization resistance and defect chemistry is beyond the scope of the present work but can be found in a separate study 20 .…”
Section: Surface-related Polarization Resistance Of Pristine Electrod...mentioning
confidence: 93%
See 1 more Smart Citation
“…It is therefore not surprising that the bias dependence of R s is also different for the measurements of this study. Moreover, the oxygen exchange rates are strongly affected by defect concentrations (holes, oxygen vacancies) , and those vary with the applied anodic bias. Finally, also some surface changes at high voltages may occur .…”
Section: Resultsmentioning
confidence: 99%
“…The PLD has been utilized to deposit porous perovskite electrodes, 157‐160 electrolytes layers such as CGO, 161,162 YSZ, 163 and SDC/LSGM bilayers 164 so far. The exact transfer of the composition of LSGM was not possible through PLD 165 .…”
Section: Fabrication Techniques For Sofcsmentioning
confidence: 99%